PROCESSING AND ANTIBACTERIAL CHARACTERIZATION OF THERAPEUTIC ION-DOPED MESOPOROUS BIOACTIVE SILICATE GLASSES (MBGS) - Kaya, Seray; Cresswell, Mark; Boccaccini, Aldo R. (EUROMAT 2017 (European Congress and Exhibition on Advanced Materials and Processes), 2017)
The first bioactive silicate glass (BG) (45S5- 46.1SiO2, 24.4Na2O, 26.9CaO and 2.6P2O5 (mol%)) was invented by Larry Hench at the University of Florida in 1969 (Hench et al., 1971)and prepared by the melt-quenching method. After his invention there has been great interest to develop new BGs and in this perspective in 2004 Yan (Yan et al., 2004)produced the first MBG by combining sol-gel and surfactant templating methods. Imparting osteogenesis, antibacterial capacity, angiogenesis or cementogenesis properties to BGs can be achieved by incorporating biologically active ions (Hoppe et al., 2011). Doping MBGs with metallic ions has been also investigated (e.g. Wu and Chang, 2012). In this study, a new family of mesoporous silicate bioactive glasses doped with varying wt% of therapeutic antibacterial ions (Ag, Cu, Ce and Zn) has been synthesized via sol-gel technique in combination with a surfactant (Pluronic P123). After successful production of the MBGs, their resistance against E. coli and S. carnosus bacteria was investigated viathe disk diffusion test. Results have shown the increase in the percentage of doping ions, the inhibition zone for the growth of bacteria. It was observed that the largest inhibition zone was obtained with copper-doped MBGs. Zinc and cerium-doped MBGs are the least bacterial resistance. The implications of these results for designing novel MBGs with antibacterial capability.